(untitled) (Damu Journal of Sport Sciences, 2024)
The study aimed to prepare rapid strength training and identify the values ​​of some physical variables in volleyball and identify the effect of rapid strength training on the values ​​of some physical variables in volleyball for the experimental group between the pre- and post-tests. As for the research hypothesis, the researcher assumed the existence of significant differences in some physical variables for the experimental group between the tests (pre- and post-test), in favor of the post-test. The researcher used the experimental method by designing two equal control and experimental groups with pre- and post-tests, in order to suit the nature of the research problem. The research community was determined intentionally, represented by players of the clubs of Maysan Governorate, second division, qualified for the first division (Maysan Oil - Qalaat Saleh - Sugar - Ali Al-Gharbi - Kamit) for the sports season (2023 - 2024), and their number is (70) players, as for the research sample, it was chosen intentionally and then divided randomly by lottery into two groups, as it was represented by the (Qalaat Saleh) Club in Maysan Governorate, and their number is (14) players, as the researcher divided the sample into two groups as follows (7) players, an experimental group, on which rapid strength training was applied prepared by the researcher, and (7) players, a control group, on which the usual method was applied. The sample constituted a percentage of (20%) of the original research community.